Thirteen and Half Syndrome in Sero-negative Neuromyelitis Optica Spectrum disorder: A Case Report (Journal of Pharmaceutical Negative Results, 2022)
Thirteen and a half syndrome is one and a half syndrome along with ipsilateral facial, trigeminal nerve lower motor neuron palsy .We describe a 33 year old man ,who developed acute onset right facial , trigeminal nerve palsy along with one and a half syndrome,thus constituting thirteen and a half syndrome , with sensory symptoms in left upper limb. MRI Brain showed T2 hyperintense andT1 hypointense lesion in right half of pons and cervicomedullary junction which was non enhancing after contrast administration.Serum antiaquaporin 4 antibodies were negative. He was diagnosed with sero-negative NMOSD .Patient improved significantly after5 cycles of plasmapheresis Only 2 cases of thirteen and half syndrome have been reported in literature so far.